Legal linguistic templates and the tension between legal knowledge representation and reasoning - Libal, Tomer (Frontiers in Artificial Intelligence, 2023)
There is an inherent tension between knowledge representation and reasoning. For an optimal representation and validation, an expressive language should be used. For an optimal automated reasoning, a simple one is preferred. Which language should we choose for our legal knowledge representation if our goal is to apply automated legal reasoning? In this paper we investigate the properties and requirements of each of these two applications. We suggest that by using Legal Linguistic Templates, one can solve the above tension in some practical situations.